Microfinance Institutions in Ekiti State: A Tool to Poverty Alleviation - Peter Oluwaseun Oyewale (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study is to examine the impact of microfinance institution to poverty alleviation in Ekiti State considering the case of LAPO- (Lift Above Poverty) in Ekiti State. To manage the data to achieve the main objective of this Study, this study takes LAPO Microfinance institution to alleviate poverty in Ekiti State in order to: Carry out an Historical analysis of LAPO microfinance; To also investigate the introduction of LAPO microfinance bank in Ekiti; To investigate the structure and organisation of LAPO microfinance bank; Finally, to determine the effect of LAPO microfinance bank on poverty alleviation in Ekiti state. The  paper  obtained  it's  data  from  both primary and secondary sources which are made up  of oral interview, books, journal articles, newspaper reports and government publications relevant  to  the  topic.